MAGNETIC RESONANCE IMAGING FINDINGS IN SEIZURE PATIENTS WITH NORMAL NEUROLOGICAL EXAMINATION - Ardalani, Ghasem Fatahzadeh; Anari, Hasan; Sadegiyeh-Ahari, Saeed; Rezvanipour, Hossein (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Background: Imaging plays a critical role in the treatment and diagnosis of individuals experiencing seizures, particularly those whose seizures cannot be explained. In various circumstances, CT scans and MRIs (Magnetic Resonance Imaging) are utilized in tandem. Objective: The purpose of this research was to evaluate the MRI findings of patients referred to Alavi Hospital with seizures and a normal neurological examination. Methods: This case-series study examined one hundred patients with epilepsy who underwent normal neurological examinations. All patients' imaging reports were meticulously examined, and any changes were documented in pre-established checklists that comprised of the following: age, gender, family history, EEG (electroencephalogram) results, neurological assessments (including motor, plantar, and tendon reflexes), and MRI findings derived from the patients' files and clinical histories. Result: In the range of 11 to 58 years, the mean age of patients was 7.46 + 32.62 years. Males comprised forty-six (46%) of the patients. In45% of the cases, a familial history of seizures was documented (n=45). Normal EEG results were obtained in 62 cases (62%). Twenty cases (20%) of abnormalities were detected on MRI, seven of which were tumor lesions, as reported by the radiologist. The imaging of the patient's brain revealed no significant correlation between the pathological findings and variables such as age, gender, or family history. No significant correlation was observed between electroencephalogram results and pathological findings on brain imaging in patients with epilepsy. Conclusion: brain imaging partially compensates for the false negatives that occur during electroencephalograms, and concurrently employing both modalities enhances the ability to diagnose underlying issues in patients experiencing seizures.